Risk assessment to Barents Sea ecosystem services: an expert-based approach - Pham, Thuy Thi Thanh; Armstrong, Claire W.; Solvang, Hiroko Kato; Skern-Mauritzen, Mette (Frontiers in Marine Science, 2025)
This study aims to investigate the risks posed by climate change and anthropogenic activities on ecosystem services in the Barents Sea, Norway. Using an expert assessment approach, we identify which ecosystem services are at high risk and the human activities and pressures contributing to these risks. The findings indicate that risks vary across ecosystem services, activities, and pressures; however, most are categorized as medium or low. Biodiversity, as a cultural service, and fish/shellfish, as a provisioning service, are identified as the two most threatened ecosystem services. In contrast, educational services are perceived as the least impacted. Temperature change is found to have the greatest impact on the services. Experts are generally uncertain about the risk levels; however, fish/shellfish and biodiversity are the two services associated with the least uncertainty. The results highlight the limited knowledge regarding risks to ecosystem services in the Barents Sea. The study emphasizes the need for future research to address these knowledge gaps and discusses where management efforts should be focused.